The Influence Of Using Extract Neem Leaf (Azadirachta indica A.juss) Soap In The Scabies lesions grade II Healing - Anis Murniati; Indah Rohmawati (Journal of Agromedicine and Medical Sciences, 2018)
Scabies is an infectious skin disease caused by infection with Sarcoptes scabiei mites. Clinical symptoms of itching in the lesions. There are herbal plants, namely the neem plant with the content of mimba leaf extract, giving a very good effect in providing resistance to mites in vitro. Mimba leaf processing can be done to make various products, including soap products. So the researchers wanted to develop the concept and knowledge of the effects of soap made from mimba leaf extract in curing lesions in scabies grade II patients in the female dormitory of Ponpes Pandanaran Ngunut Tulungagung. This study uses the Quasy Experiment design with an experimental design of Non equivalent control group design. The treatment group was divided into two treatment groups, namely the treatment using neem leaf extract soap (Azadirachta indica A. juss) and using antibacterial soap. The sample was determined using purposive sampling according to the inclusion criteria, as many as 70 respondents. The assessment used observation sheets of lesion wounds according to the modified Bates-jensen wound assessment tool. The results of the analysis of 70 respondents obtained the results of independent t-test statistics obtained a significance value of p (value) = 0,000. The use of solid soap mimba leaf extract (Azadirachta indica A. juss) in dealing with scabies with Azadirachtinya content which is able to provide resistance to mites by inhibiting the life cycle (metamorphosis). Keywords: Scabies, neem leaves, lesions, healing